Procalcitonin in amniotic fluid at the time of genetic amniocentesis and preterm delivery. (18th October 2018) - Bilinski, Robyn T.; Williams, Shauna F.; Apuzzio, Joseph J.
Abstract: Purpose: Procalcitonin (PCT) is an acute-phase protein that has been infrequently studied in amniotic fluid. We sought to determine if PCT levels measured in amniotic fluid samples at the time of genetic amniocentesis are predictive of preterm delivery. Materials and methods: A retrospective cohort study was performed on all women presenting for genetic amniocentesis between 15–23 weeks of pregnancy at our institution from 2011 to 2013 with stored amniotic fluid samples. PCT protein levels were measured in the samples by enzyme-linked immunosorbent assay (ELISA). PCT levels in women who delivered less than 37 weeks versus those who delivered at or after 37 week were compared. Mann–Whitney test was used. Results: Eighty-seven samples were available for analysis and of these eight (9.2%) were from patients who delivered preterm. Sixty-two (70%) had PCT levels below the lower limit of quantification, which was 25 pg/mL. Median PCT levels did not differ between the preterm and term group [20.4 pg/mL (range 0–82.8) and 20.2 pg/mL (range 0–198.4), respectively, p  = .95]. Conclusion: In asymptomatic women undergoing genetic amniocentesis in this cohort, procalcitonin levels were low to undetectable and did not correlate with risk of subsequent preterm birth.